Differences in the Effectiveness of Kicks Using the Instep with Toe Feet Against the Results of Shooting Accuracy Second Penalty at Futsal UKM Universitas Muhammadiyah Surakarta - Dwi Adiyana Bayu Kristiyadi; Gatot Jariono (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
In the futsal game requires the ability to perform basic ball shooting techniques or shooting, where shooting techniques are the basic techniques that are very important in helping to score goals.  The shooting technique itself consists of kicks using the instep and toe, where the two techniques produce different shooting accuracy. Therefore, the purpose of this study is to see the difference in the effectiveness of kicks using the instep and toe against the results of the accuracy of shooting the second penalty in futsal UKM  at Muhammadiyah University of Surakarta. This study uses a type of comparative study comparing two different variables applied to one object.  The data collection technique in this study used two-second penalty kick tests.  After all the data were obtained, a descriptive analysis was carried out, then continued with the prerequisite test using the normality test and test homogeneity which was then tested hypotheses. All data tests were carried out using the help of SPSS, with the conclusion that shooting using the instep is more effective than shooting using the toe in shooting Second Penalty.  Where it was shown that the average result of the shooting group using the instep was better than the shooting group using the toe, with an average difference of 10.25.